Development and Evaluation of Polymethacrylate-Based Ophthalmic Nanofiber Inserts Containing Dual Drug-Loaded Dorzolamide and Timolol: In Vivo Study in Rabbit’s Eye - Ahmad Karami; Shahla Mirzaeei; Leila Rezaei; Ali Nokhodchi (Biomedicines)
Background/objectives: The aim of the study was to create a nanofiber insert incorporating Timolol (TIM) and Dorzolamide (DOR), targeting the management of glaucoma. This condition encompasses a variety of chronic, advancing ocular disorders typically associated with elevated intraocular pressure (IOP). Methods: The insert was made of Eudragite RL100 (EUD) polymer, a biocompatible material with high bioavailability, using the electrospinning method. The inserts were studied for morphology, drug–polymer interaction, physicochemical properties, and in vitro drug-release study. The pharmacokinetic properties of fibers were examined alongside consideration for irritation using a rabbit model and cell compatibility. Results: The results of the in vitro drug-release test showed retention and controlled release of both DOR/TIM over 80 h. Morphological examination demonstrated uniform nanofibers with mean diameters < 465 nm. The cell compatibility test showed a high percentage of cell survival, and none of the formulations irritated the rabbit’s eye. The Area Under the Curve (AUC0-72) for DOR and TIM in EDT formulations was approximately 3216.63 ± 63.25 µg·h/mL and 2598.89 ± 46.65 µg·h/mL, respectively, with Mean Residence Times (MRTs) of approximately 21.6 ± 0.19 h and 16.29 ± 6.44 h. Conclusions: Based on the results, the dual drug-loaded nanofiber preservative-free system can potentially be a suitable alternative to eye drops and can be used to reduce fluctuation and dose frequency.